STRATEGY OF THE REGIONAL DISASTER MANAGEMENT AGENCY IN FLOOD DISASTER MANAGEMENT IN MANDAILING NATAL REGENCY - Nasution, Muhammad Taufik; Lubis, Maksum Syahri; Sembiring, Walid Musthafa (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study analyzes the strategy of the Regional Disaster Management Agency (BPBD) of Mandailing Natal Regency in managing flood disasters. The focus of this research includes four main stages: mitigation, preparedness, emergency response, and post-disaster recovery. The research method used is qualitative with a case study approach, through in-depth interviews, observations, and documentation analysis. The results of the study show that BPBD has implemented various strategies, such as river normalization, embankment construction, community education, the formation of volunteer teams, and the provision of an early warning system. However, constraints such as budget constraints, hard-to-reach geographical conditions, and low community participation hampered the effectiveness of this strategy. In the emergency response phase, BPBD coordinated with various agencies for evacuation and aid distribution, although access to some remote areas was still limited. In the recovery stage, BPBD carries out infrastructure rehabilitation and economic empowerment for affected residents, but this process is also constrained by limited funds. Overall, the BPBD strategy is considered quite comprehensive, but it needs to be strengthened in terms of collaboration between institutions, resource capacity building, and community-based approaches so that flood disaster management is more optimal. This study provides recommendations to improve the effectiveness of flood management strategies in Mandailing Natal.